Effects of large openings in the shear zone of reinforced concrete beams - Choo, C.-S. (Construction Research Institute of Malaysia, 2013)
Openings are of ten provided in reinforced concrete (RC) beams to facilitate the passage of utility pipes and ducts to accommodate essential services in buildings either commercial or residential. They are usually provided by structural engineers in the bending zone (safe zone) to avoid the beams from losing their original beam capacities. However, there are situations when Mechanical and Electrical (M&E) engineers requested to provide openings at critical locations of RC beams to simplify the arrangements of pipes and ducts. This paper provides an investigation to study the effects of large openings (circular and square) in the shear zones of RC beams. Seven beams were tested to failure under four-points loading. The beam specimens had a cross-section of 120 mm Ã300 mm and a total length of 2000 mm. The openings were provided at both ends; at distances 0, 0.5d, and d from the beam supports. The experimental results were validated using a finite element (FE) program, ATENA. Results show that these openings at the studied locations have significantly reduced the beam capacity to approximately 70-80. Comparison of experimental and FE results in terms of crack patterns and load-deflection behaviour were presented and discussed. Agreeable results in terms of crack patterns and load-deflection curves were obtained between the experimental and FE results; about 50-60 and 15-20, respectively.